Covid-19 dan The Stock Reaction Of Islamic Banking In Asia - Asykarulloh, Azam; Sultoni, Hasan (Musyarakah: Journal of Sharia Economic (MJSE), 2024)
The number of COVID-19 cases that hit Asia also put pressure on the economy and turmoil in several stock markets. This study aims to see the reaction of Islamic banking stocks in Asia to the announcement of COVID-19 as a global pandemic by WHO. This research uses an event study method with an observation period of 10 days after and before the event day. Data were obtained through the stock trading website, and 43 banking samples from 11 countries were observed. Data analysis used One-Sample T-Test, Paired Sample T-Test, One Sample Wilcoxon Signed Rank Test, and Paired Sample Wilcoxon Signed Rank Test with the help of SPSS 21.0 tools. The results showed that there was a significant AAR around the event days. And there is a difference in CAAR before and after the event day. These results were accompanied by a negative CAAR value after the event period, which confirmed that Islamic banking stocks in Asia responded negatively to the announcement of COVID-19 by WHO. The robustness test results show that ASEAN is the most reacted region compared to the GCC, South Asia, and other areas.